Protein p 16INK4A expression in cervical intraepithelial neoplasia and invasive squamous cell carcinoma of uterine cervix - Gupta Ruchi; Srinivasan Radhika; Nijhawan Raje; Suri Vanita; Uppal Radha (Indian Journal of Pathology and Microbiology, 2010)
The association of human papilloma virus (HPV) infection and cervical intraepithelial neoplasia (CIN) is well recognized. Interaction of HPV oncogenic proteins with cellular regulatory proteins leads to up regulation of p16 INK4A , a CDK inhibitor, which is a biomarker for HPV infection. We investigated p16 expression in CIN and invasive squamous cell carcinoma (SCC) which has not been reported in the Indian population previously. Materials and Methods: Retrospective analysis of 100 cases with 20 cases each of histologically normal cervical epithelium, CIN1, 2, 3 and invasive SCC for p16 expression was performed by immunohistochemistry using commercially available mouse monoclonal antibody to p16 (clone 6H12). Statistical Analysis: For differences in expression among groups, statistical analysis was carried out using ANOVA and post hoc test of Scheffe. Results: p16 immunoreactivity was found to be both nuclear and/or cytoplasmic. The normal cervical epithelium was predominantly negative for p16 (18/20). There was a progressive increase of p16 expression with the grade of CIN. In CIN 1, two cases (20%) showed nuclear and nucleocytoplasmic positivity respectively. In contrast, diffuse strong nuclear or nucleocytoplasmic expression was observed in 45 and 55% cases of CIN 2 and CIN 3 respectively. All except one squamous cell carcinoma stained strongly positive for p16. The difference in expression between CIN 2/3 and SCC versus normal cervix was found highly significant (p is equal to 0.008 and p less than 0.001). Conclusions: p16 expression correlates excellently with the grade of CIN and is a sensitive marker of cervical intraepithelial neoplasia.